Philosophy, politics, and Austrian economics (Advances in Austrian economics, 2020)
Philosophy, Politics, and Economics, as an interdisciplinary endeavour, has surged in popularity in recent years. Work in this field usually draws on standard microeconomics to grapple with questions from political philosophy. But what might Austrian economics, which provides an alternative approach, have to offer to this endeavour?